The use of the definite article in prepositional phrases in South Central Romani - Bodnárová, Zuzana (Romano džaniben, 2020)
The aim of this paper is to describe the linguistic changes which have led to the simplification of the definite article paradigm, or even to the entire loss of the definite article, in prepositional phrases of various South Central Romani varieties. I will try to identify the linguistic processes that may underlie these changes, such as analogy or contact-induced phenomena. In regard of the latter, I will discuss some of these changes in the wider context of the decline of gender and number marking in South Central Romani varieties in contact with Hungarian.